Abordagens teórico-metodológicas da alfabetização e formação de professores - Kuiawinski, Cláudia Fátima (2007)
This paper attained a historical recapture from the formation process of elementary professors in Brazil until today, exploiting different knowing required to the elementary professor, the articulation from the theory and from the handy and the importance of the initial and continued formation about doing a good job. Picked still, to rebuild studies in the educational area, focusing it in three looks: the Interacionist prospect, the Lyrics prospect and the Professor or Educational prospect. The first category entry the studies in Emilia Ferreiro, the second category receives the hangs as of Magda Soares and her collaborators and the third category was based in the assignments of the group leaded by Regina Leite Garcia. Based in the theoretical reconstruction of the approaches and in a research with an exploratory character focusing in analyse the crate curricular from four Educational Institutions that graduate teachers in the north of Rio Grande do Sul, and explore the continuities and discontinuities existing between both, it was analyzed the subjects that informs about the acquirement of the written language, and the presence of those theoretical studies, considered in this paper, necessary to the initial formation of elementary teachers. By the obtained results, we understood that each occupational professor must consider the formation continued not just as an actualization bu also as a complement for the background acquired at the formation, then teachers can aggregate the theoretical - methodological elements and also their experiences making possible the improvement in the process of teaching and learning.